KOMPETENSI PERADILAN TATA USAHA NEGARA BERDASARKAN UNDANG-UNDANG TENTANG ADMINISTRASI PEMERINTAHAN - Bakar, Dian Utami Mas; Muin, Audyna Mayasari (The Juris, 2018)
The existence of the Administrative Court becomes a necessity in a legal state in order to ensure that the Decision and/or the Acts of the Agency and/or Government Officials on Citizens can not be conducted arbitrarily. The enactment of Government Administration Act implies the competence of Administrative Courts. Some of the arrangements governing the competence of the Administrative Court are not done through the amendment of Administration Courts Act itself but through the Administration of Government Act, so that in this Act contains provisions of competence changes and even additional competence of the Administrative Court.